Transcriptomics and metabolomics analyses identified key genes associated with sugar and acid metabolism in sweet and sour pomegranate cultivars during the developmental period - Feng, Lijuan (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.